The legend of the Easter egg - Walburg, Lori.; Bernardin, James (Grand Rapids, Mich. : Zondervan, 1999)
While preparing for Easter in his small prairie town, Thomas hears the story of the resurrection of Jesus and discovers the meaning of new life through the symbolism of the Easter egg. Includes an information page about the traditions and symbols of Lent and Easter.
2.6
K-3
Keywords: Easter eggs -- Fiction; Easter -- Fiction; Jesus Christ -- Resurrection -- Fiction; Christian life -- Fiction; Easter eggs -- Fiction; Easter -- Fiction; Jesus Christ -- Resurrection -- Fiction; Christian life -- Fiction